Analysis of Urban Spatial Planning Implementation in the Wania Riverbank Area in Asmat Paumako Village, Timika, Papua, Indonesia - Yeni Elmas, Yuliana; Roberth KR Hammar; Yusty F. Rahawarin (Golden Ratio of Law and Social Policy Review, 2025)
This study aims to analyze the implementation of urban spatial planning in the Wania Riverbank area, Asmat Paumako Village, Timika, Papua, explicitly focusing on the factors influencing policy implementation and the resulting socio-ecological impacts. Using a qualitative descriptive method with a field study approach, this study explores in depth the relationship between formal spatial planning policies and the local wisdom practices of the Asmat indigenous community. Primary data were obtained through in-depth interviews, participatory observation, and relevant secondary documents such as the Detailed Spatial Planning Plan and related regional regulations. This approach allows for a holistic understanding of the constraints and opportunities in spatial planning implementation in an area with unique socio-cultural and ecological characteristics. The research results show that implementing spatial planning in the Wania Riverbank area faces various obstacles, including weak communication and coordination between government agencies, limited technical and financial resources, and differences in paradigms between the Asmat community's customary legal system and formal government regulations. The inconsistency of spatial utilization practices with the official provisions in the Detailed Spatial Plan leads to the risk of ecological degradation, such as a decline in the function of riverbank habitats, increased vulnerability to flooding, and the emergence of social conflict. In addition, the research emphasizes the importance of recognizing and integrating local wisdom in the spatial planning and management process to increase the effectiveness of implementation and social legitimacy. These findings also reinforce George Edward III's policy implementation theory, which emphasizes the importance of effective communication, resource availability, and implementer disposition for successful implementation, and supports an inclusive and sustainable urban planning approach that balances physical, social, and ecological aspects. This research provides important empirical and conceptual contributions to formulating spatial planning policies in regions with complex socio-cultural and ecological characteristics, such as Papua, while emphasizing the need for a multisectoral, participatory, and adaptive approach to urban space management. Therefore, this research is a strategic foundation for local governments, communities, and other stakeholders in harmoniously and sustainably managing riverbank areas for inclusive and environmentally friendly development.